Analisis Aspek K3 serta Perancangan Ulang Tata Letak Industri Tahu di Kota Semarang “Sukses Sejatera” - Firda Aulia Nisawati; Rois Fatoni (Jurnal Syntax Admiration, 2025)
This study aims to analyze Occupational Health and Safety (OHS) aspects and redesign the layout of the "Sukses Sejahtera" tofu industry in Semarang City. The research employs a qualitative method with a descriptive approach, involving field observations, interviews, and literature studies. The findings reveal that workers' knowledge regarding the use of Personal Protective Equipment (PPE) is limited, and there is a lack of training on the potential hazards of steam boiler operation. In the layout redesign, the third proposal was selected due to its material handling efficiency of 11.60 meters, reduced hazard potential, and improved inter-process connectivity in production. This research provides recommendations to enhance operational safety and facility layout efficiency in the tofu industry.